GAMBARAN TINGKAT PENGETAHUAN SISWA SEKOLAH DASAR TENTANG PERAWATAN KESEHATAN GIGI DI LAHAN GAMBUT DESA PULAU MUDA - Tengku Hidayu Marizal; Arneliwat Arneliwat; Rismadefi Woferst (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2023)
Dental health can be influenced by many factors, including environmental factors and the level of knowledge about dental health care. The purpose of this study was to describe the level of knowledge of elementary school students about dental health care in the peatlands of Pulau Muda village. The research design was a descriptive study at public elementary schools in Pulau Muda village. Collecting data with stratified random sampling as many as 141 students. Measuring tool in the form of a questionnaire that has been tested for validity and reliability. The results found that most respondents were in the fifth grade (55%), aged 11 years (39%), while the sex was dominated by men (52%). The description of the level of knowledge about dental health care is good (52%). More specifically the level of knowledge about tooth brushing behavior was found to be good (77%) and dental caries prevention diet at a good level (56%). While the level of knowledge about dental examinations was found to be lacking (38%). The results of the study showed that the respondents had good knowledge of dental health care, but they still did not know about dental examinations.